IFNL4 ss469415590 Variant Is Associated with Treatment Response in Japanese HCV Genotype 1 Infected Individuals Treated with IFN-Including Regimens. (8th December 2014) - Miyamura, Tatsuo; Kanda, Tatsuo; Nakamoto, Shingo; Arai, Makoto; Nakamura, Masato; Wu, Shuang; Jiang, Xia; Sasaki, Reina; Haga, Yuki; Yasui, Shin; Ooka, Yoshihiko; Chiba, Tetsuhiro; et al.
Abstract : Aim . Eradication of hepatitis C virus (HCV) is still challenging even if interferon- (IFN-) free regimens with direct-acting antiviral agents (DAAs) for HCV-infected individuals are available in clinical practice. IFNL4 is a newly described protein, associated with human antiviral defenses. We investigated whether IFNL4 ss469415590 variant has an effect on the prediction of treatment response in HCV-infected patients treated with IFN-including regimens. Patients and Methods . In all, 185 patients infected with HCV genotype 1 treated with peg-IFN plus ribavirin, with or without telaprevir, were genotyped for IFNL4 ss469415590. We retrospectively investigated whether the role of IFNL4 ss469415590 variant and other factors could predict sustained virological response (SVR) in Japanese patients infected with HCV genotype 1. Results . There were 65.7%, 31.5%, and 2.8% patients in the IFNL4 ss469415590 TT/TT, TT/-G, and -G/-G groups, respectively. SVR rates were 82.1% or 49.3% in patients treated with peg-IFN plus ribavirin with or without telaprevir, respectively. IFNL4 ss469415590 variant and HCV viral loads or IFNL4 ss469415590 variant and early virological response were better predictors of SVR in patients treated with peg-IFN plus ribavirin with or without telaprevir, respectively. Conclusion . In the era of DAAs, measurement of IFNL4 ss469415590 variant could help the prediction of SVR in Japanese HCV genotype 1 infected individuals treated with IFN-including regimens.